Topography Amplified Spatiotemporal Asynchrony in Grassland NPP Responses to Climate Change in the Three-River Headwaters Region - Zhudeng Wei; Meiyan Qu; Minyan Wang; Wenzheng Yu (Remote Sensing)
Grassland productivity is crucial for sustainable alpine livestock farming, yet the combined effects of climate change and topography remain unclear. Using long-term time series data of grassland NPP derived from Landsat imagery, along with meteorological and DEM data, this study employed correlation analysis and SEM to quantify climate-driven grassland NPP dynamics and topography-mediated regulatory effects in the Three-River Headwaters Region between 1990 and 2020. Significant spatiotemporal dynamics of grassland NPP were found in response to climate change over the past thirty years. Grassland NPP declined before 1994 and then grew significantly after 1995 at an average rate of 0.88 gC·m−2·a−1 (p < 0.01). Spatially, NPP increased in 69% of the region, with significant and highly significant growth in 9.5% (p < 0.05) and 35.7% (p < 0.01), mainly in the southeast. Driven by general warming and wetting, topographic modulation of hydrothermal conditions had intensified a mismatch in both time and space between grassland NPP and climate change, particularly in temperature sensitivity. The positive effect of temperature on NPP shifted to higher elevations (4000–5000 m) and lower slopes (5–25°), with NPP at higher elevations exhibiting greater sensitivity to temperature changes. However, the most substantial contributions to the overall rise in NPP occurred at altitudes of 3000–4000 m and slopes of 0–25°. The key mechanism is that NPP growth above 4000 m was constrained by precipitation scarcity despite thermal limitation alleviation from warming. Overall, the direct effects of climate change outweighed those of various topographic factors, with both showing slight declines since 2010. These findings highlight the need for differentiated governance, restoration, and adaptive management of grasslands across diverse topographic gradients.